Erythrocyte enzymes of Glyoxalase system as indicators of beneficial effects of antihyperglycemic agents in Type 2 Diabetes - Patke, Vinay; Saroj, Sarvesh (International Journal of Research in Medical Sciences, 2017)
Background: Methylglyoxal (MG), a product of sustained hyperglycemia, is a reactive carbonyl toxin responsible for development of complications in diabetes. Glyoxalase system detoxify MG to prevent complications. Some antihyperglycemic agents, may inhibit deleterious effects of MG by independent mechanisms. It was considered worthwhile to identify such agents and to find out whether changes observed in the erythrocyte levels of Glyoxalase I, Glyoxalase II, Aldose Reductase & D-Lactate are indicators of the beneficial effects through their direct action on MG, or merely a result of good glycemic control in response to treatment. Methods: The glyoxalase system was characterized in erythrocytes of blood samples from patients with Type 2 Diabetes (n = 147), and normal healthy control subjects (n = 40). Diabetics were divided into groups based on presence or absence of complications; & further divided into subgroups based on medication with sulphonylurea, metformin, insulin and combination therapy. Results: Erythrocyte Glyoxalase I, Glyoxalase II, Aldose Reductase, and D-Lactate levels significantly increased in all diabetics, (p<0.001) relative to controls. A maximum rise of enzymes in T2D with complications was observed as compared to patients without complications (p<0.001). Inadequate glycemic control was observed in all diabetics, and enzyme levels significantly declined in groups treated with metformin, either as monotherapy or in combination with insulin. Conclusions: Enzymes of Glyoxalase system indicate beneficial effects of metformin. Metformin reduces MG and minimizes worsening glycemic control leading to complications. Metformin renders protection through mechanism independent of its antihyperglycemic action.